Research Progress on the Regulation Mechanism of Key Signal Pathways Affecting the Prognosis of Glioma - Wu, Hao; Wei, Min; Li, Yuping; Ma, Qiang; Zhang, Hengzhu (Frontiers in Molecular Neuroscience, 2022)
As is known to all, glioma, a global difficult problem, has a high malignant degree, high recurrence rate and poor prognosis. We analyzed and summarized signal pathway of the Hippo/YAP, PI3K/AKT/mTOR, miRNA, WNT/β-catenin, Notch, Hedgehog, TGF-β, TCS/mTORC1 signal pathway, JAK/STAT signal pathway, MAPK signaling pathway, the relationship between BBB and signal pathways and the mechanism of key enzymes in glioma. It is concluded that Yap1 inhibitor may become an effective target for the treatment of glioma in the near future through efforts of generation after generation. Inhibiting PI3K/Akt/mTOR, Shh, Wnt/β-Catenin, and HIF-1α can reduce the migration ability and drug resistance of tumor cells to improve the prognosis of glioma. The analysis shows that Notch1 and Sox2 have a positive feedback regulation mechanism, and Notch4 predicts the malignant degree of glioma. In this way, notch cannot only be treated for glioma stem cells in clinic, but also be used as an evaluation index to evaluate the prognosis, and provide an exploratory attempt for the direction of glioma treatment. MiRNA plays an important role in diagnosis, and in the treatment of glioma, VPS25, KCNQ1OT1, KB-1460A1.5, and CKAP4 are promising prognostic indicators and a potential therapeutic targets for glioma, meanwhile, Rheb is also a potent activator of Signaling cross-talk etc. It is believed that these studies will help us to have a deeper understanding of glioma, so that we will find new and better treatment schemes to gradually conquer the problem of glioma.